Methanolic Extract of Plumbago Zeylanica - A Remarkable Antibacterial Agent Against Many Human and Agricultural Pathogens - Mukesh Kumar Singh; Ajit Pandey; Hemant Sawarkar; Anshita Gupta; Bina Gidwani; Hemant Dhongade; Dulal Krishna Tripathi (Korean Pharmacopuncture Institute, 2017)
Objectives: The current investigation was carried out to determine the cytotoxic and the antimicrobial activities of methanolic extracts of Plumbago zeylanica. Methods: The stems, leaves, and whole plants were air dried and extracted with methanol by using a Soxhlet extractor for 72 hours at 55 - 60°C. The antimicrobial activities were determined from the zones of inhibition, which were measured by using the agar well diffusion method, and the cytotoxicity assays were performed using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay method. Results: The methanolic extracts of the stem and the leaves of Plumbago zeylanica were tested against six bacterial species and nine fungal species, and both extracts showed antimicrobial activity in a dose-dependent manner. The leaf extract of Plumbago zeylanica showed maximum antimicrobial activity against both Staphylococcus aureus sub sp aureus and Fusarium oxysporum. The stem extract was found to be more antimicrobial against the Pseudomonas aeruginosa and the Penicillium expansum species. MTT assays were used to test the cytotoxicity of the whole plant extract in the HCT-116 and the K-562 cell lines, and that extract was shown to have weak cytotoxicity in both cell lines. Conclusion: In the present study, the methanolic stem extracts of Plumbago zeylanica were found to possess remarkable antibacterial activities against many human and agricultural pathogens. The extracts were also found to possess significant antifungal activities, but the antifungal activities were less than the antibacterial activities. Finally, the extracts were found to have weak cytotoxicities in the HCT-116 and the K-562 cell lines.